The Relationship Between Personality and Teaching Effectiveness of English Teachers from the Perceptions of Students at Dianchi College of Yunnan University in Kunming, Yunnan Province, China - Zhai, Xiaowen; Karnjanapun, Supit (Scholar: Human Sciences, 2021)
This study was conducted to identify whether there was a significant relationship between personality and teaching effectiveness of English teachers from the perceptions of students at Dianchi College of Yunnan University in Kunming, Yunnan Province, China. The Big Five Inventory, which was originally designed by John and Srivastava (1999), was used for measuring the level of personality of English teachers at Dianchi College of Yunnan University in Kunming, Yunnan Province, China. Student Instructional Report II, which was originally designed by Centra (1972), was used for measuring the level of teaching effectiveness of English teachers at Dianchi College of Yunnan University in Kunming, Yunnan Province, China. Ninety students participated in this study, which were conducted during the academic year 2018-2019. The data were collected and analyzed by a statistical software program. According to the purpose and hypotheses of the study, different statistical methods were used to analyze the data (e.g., means, standard deviations, and correlational analysis using multiple correlation coefficient). The study showed that the personality of English junior teachers at Dianchi College of Yunnan University contain agreeableness, conscientiousness, extraversion, neuroticism and openness. The study also showed that the level of teaching effectiveness of English teachers at Dianchi College of Yunnan University was effective. The results showed that there was a significant relationship between personality and teaching effectiveness of English teachers from the perceptions of students at Dianchi College of Yunnan University in Kunming, Yunnan Province, China.